Neutrophilia in the bronchoalveolar lavage fluid increases coughing during flexible fiberoptic bronchoscopy in a pediatric cohort - Danino, Laura; Stehling, Florian; Eckerland, Maximilian; Orhan, Eser; Tschiedel, Eva (Frontiers in Pediatrics, 2024)
Objective: This study is an addition to the already published prospective randomized double-blinded trial by Tschiedel et al. (1) that compared two different sedation regimes in fiberoptic flexible bronchoscopy in pediatric subjects. The presented study's objective was to analyze the correlation between the neutrophil percentage of bronchoalveolar lavage fluid (BALF) and coughing episodes during bronchoscopy. Methods: Fifty subjects, aged 1 to 17 years, received flexible fiberoptic bronchoscopy under deep sedation. BALF of 39 subjects was analyzed regarding cytology and microbiology.The percentage of neutrophils from the total cell count ranged from 0 to 95.3 % (median 2.7). Nineteen patients (49 %) had a percentage of ≥ 3.0 %. Pearson's correlation showed a high correlation (r = 0.529, p = 0.001) between the coughing episodes per minute and the neutrophil percentage in the BALF. ANOVA showed a significant difference for neutrophil percentage between the indication groups (p = 0.013). The t-test (p = 0.019) showed a significant difference between the neutrophil percentage for patients with a probable airway infection under immunosuppression (median 2.9) and the patients with cystic fibrosis (median 49.6). The linear regression showed a significantly stronger impact of the neutrophils' percentage than the sedation regime on coughing frequency (ßneutrophils = 0.526 with p = 0.001 vs. ßsedation = 0.165 with p = 0.251).When bronchoscopy is to be performed in a pediatric patient with suspected bacterial or viral infection and therefore neutrophilic airway inflammation, coughing is to be expected during the procedure.